Improving Learning in Undergraduate Physics Using Integrated 'Studio' Environments to Replace Traditional Lectures, Laboratories and Tutorials. Final Report for a 1997 National Teaching Development Grant. - Loss, Robert D. (Committee for University Teaching and Staff Development, 1997)
Final report of a project at Curtin University, Department of Applied Physics. This two-year project introduced studio instruction to the teaching of the five major units undertaken by first year students majoring in Geophysics, Physics and Physics/Engineering. Studio instruction uses team teaching and student-centered, discovery type learning activities, integrated with information technology tools to replace conventional lectures, labs and tutorials. The studio environment trialled in this project was based largely on the Rensselaer Polytechnic Institute (RPI) 'Studio' learning environment.